Pra-produksi Fotografi Konseptual “Tangan Ibu” dengan Sentuhan Tradisional Jawa - Citra Ratih Prameswari; Wahyu Aninda Sefalya (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Pre-production photography is a comprehensive stage of preparation and planning before the production and post-production stages. This stage includes determining ideas, visual concepts, technical planning, location selection, and budget and schedule management. This stage is crucial to ensure the smooth running and success of production by minimising problems during shooting. Conceptual photography is photography with a design that carries a specific concept. This type of photography is included in fine art photography, which focuses on conveying ideas and abstract feelings through images. The resulting photographs prioritise the idea behind the work and often use imagination. The pre-production stage of the conceptual photography ‘Mother's Hands’ depicts mothers as loving and strong figures who maintain their identity as women with traditional Javanese nuances. This work conveys a message about the balance between domestic roles and self-esteem and reflects cultural values. The balance between the roles of woman and mother is the concept. The mother is the bearer of household responsibilities and an educator, while also being a woman who maintains her dignity and appearance with grace as a form of self-respect. Visually, this photographic work presents a Javanese mother who is a housewife and her accomplished daughter, who is the result of her mother's upbringing. The photoshoot took place indoors, with gebyok accents and other supporting props in line with the concept. The final result of the conceptual photography ‘Tangan Ibu’ is a photo that combines aesthetic and narrative elements through a meaningful visual presentation. This work provides an experience that is not only visually appealing but also invites emotional engagement from the audience. It can also serve as a reference for photography.